Estimation of triple prognostic factors: serum ferritin, D-dimer and HbA1c levels in post-COVID mucormycosis patients: a cross-sectional observational study - Nishant Gupta; Siddharth Nirwan; Pawan Singhal; Samta Verma; Mansi Raj; Jitendra Kumar Jangir; Kailash Singh Jat; Anjani Kumar Sharma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: India was furiously hit by the second wave of COVID-19 that peaked during the months of April and May 2021. It led to an unprecedented number of rhino-orbital-cerebral mucormycosis cases that came as a bitter surprise. Several parameters were found to be consistently elevated in the patients like serum ferritin, D-dimer, and HbA1C. Methods: A cross-sectional observational study was conducted at the SMS medical college that included 120 patients presenting with post-COVID mucormycosis from 1st May to 31st May 2021. HbA1c, D-dimer, serum ferritin levels were measured at the time of admission. Results: Our study showed a mean range of serum ferritin of 539.6±484.9, mean D-dimer range was 636.3±303.5, both of which were higher than normal. In the present study 94.1% of the patients had diabetes mellitus. Among them 60.80% of the patients had newly detected diabetes and 33.30% were known cases of diabetes with mean HbA1c 9.7±2.3. The p value was less than 0.001 which was statistically significant. Conclusions: Timely detection and categorization of the patients based on severity of the above parameters can not only help in executing the existing institutional resources but can also help in saving valuable lives, and preventing radical surgical procedures like orbital exenteration and maxillectomy.